PRELIMINARY CONSIDERATIONS ON THE CISTERNS OF THE JIZZAKH OASIS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses the cisterns and their construction, which were built in the territory of the Jizzakh oasis and occupied a worthy place on the trade caravan routes. The YYogocli, Mirzarabat and Yakka cisterns in the oasis are among the water structures that have solved the water-related problems of merchants and tourists during their operation.